Intensifying Goal-Setting Interventions for Students With Emotional and Behavioral Disorders. (April 2021) - Kumm, Skip; Maggin, Daniel M.
Goal setting is a research-informed intervention that has demonstrated improved behavioral outcomes for students with emotional and behavioral disorders. However, not all students will respond to goal-setting interventions delivered in a standard format, requiring planning, implementation, and ongoing evaluation of more intensive goal-setting formats. This article describes how teachers can implement goal-setting interventions in their classrooms and provides a systematic framework for teachers to use individualized data to intensify goal-setting interventions.